2016
DOI: 10.1590/2358-2936e2016028
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of a freshwater amphipod from South America (Crustacea, Amphipoda, Hyalellidae)

Abstract: Th is study aimed to characterize the population dynamics of Hyalella bonariensis Bond-Buckup, Araujo & Santos, 2008 from headwater spring in a rural area of state of Rio Grande do Sul, Brazil. Four samples were collected in August (winter) and October (spring) of 2012 and January (summer) and April (autumn) of 2013. Ovigerous females and precopula pairs were separated from other individual in the fi eld. A total of 5,266 specimens were sampled, being 1,878 males, 2,073 females (including 240 ovigerous females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…In the last few years, understanding of American's Hyalella has risen with an increasing number of taxonomic publications, indicating that there is still a large number of species unknown to science (González and Watling, 2002a, 2002b, 2003a, 2003bBaldinger, 2004;Pereira, 2004;González et al, 2006;Cardoso et al, 2011;Bueno et al, 2013;Rodrigues et al, 2014;Cardoso et al, 2014;Colla and César, 2015). In Brazil, most studies of Hyalella concern new species descriptions (Bastos- Pereira and Bueno, 2013;Bueno et al, 2013;Cardoso et al, 2014;Bueno et al, 2014;Streck et al, 2017), however, knowledge on their life cycles, population biology e reproductive biology are limited by the studies of Castiglioni and Bond-Buckup (2008a) (Hyalella castroi González, Bond-Buckup andAraujo, 2006 andHyalella pleoacuta González, Bond-Buckup andAraujo, 2006), Castiglioni et al (2016) (Hyalella bonariensis Bond-Buckup, Araujo and Santos, 2008) and Ozga and Castiglioni (2017) Streck and Castiglioni, 2017). Most of the remaining studies published on population, reproductive, systematic, and taxonomic aspects of Hyalella species were performed with the North American species H. azteca (Cooper, 1965;Wellborn, 1994;Grosso and Peralta, 1999;Wellborn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, understanding of American's Hyalella has risen with an increasing number of taxonomic publications, indicating that there is still a large number of species unknown to science (González and Watling, 2002a, 2002b, 2003a, 2003bBaldinger, 2004;Pereira, 2004;González et al, 2006;Cardoso et al, 2011;Bueno et al, 2013;Rodrigues et al, 2014;Cardoso et al, 2014;Colla and César, 2015). In Brazil, most studies of Hyalella concern new species descriptions (Bastos- Pereira and Bueno, 2013;Bueno et al, 2013;Cardoso et al, 2014;Bueno et al, 2014;Streck et al, 2017), however, knowledge on their life cycles, population biology e reproductive biology are limited by the studies of Castiglioni and Bond-Buckup (2008a) (Hyalella castroi González, Bond-Buckup andAraujo, 2006 andHyalella pleoacuta González, Bond-Buckup andAraujo, 2006), Castiglioni et al (2016) (Hyalella bonariensis Bond-Buckup, Araujo and Santos, 2008) and Ozga and Castiglioni (2017) Streck and Castiglioni, 2017). Most of the remaining studies published on population, reproductive, systematic, and taxonomic aspects of Hyalella species were performed with the North American species H. azteca (Cooper, 1965;Wellborn, 1994;Grosso and Peralta, 1999;Wellborn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This feature may be related to the seasonal reproduction and, consequently, to the recruitment peaks in the population. This pattern of population frequency distribution is common in other species of Hyalella such as H. azteca (Pickard & Benke 1996), H. pleoacuta and H. castroi (Castiglioni & Bond-Buckup 2008a), H. bonariensis (Castiglioni et al 2016) and H. georginae and H. gauchensis (Ozga et al 2018). According to Appadoo & Myers (2004), bimodal distributions are apparently advantageous since recruitment occurs in warmer months, when food availability is higher, increasing the survival rate.…”
Section: Discussionmentioning
confidence: 57%
“…Later, individuals were identified and grouped into four categories: juveniles (specimens with undeveloped secondary sexual character), males (individuals with a well-developed gnathopod 2), females (individuals with oostegites and a small gnathopod 2), and ovigerous females (females carrying eggs or juveniles in the brood pouch) (Borowsky 1991;Castiglioni & Bond-Buckup 2008a;Castiglioni et al 2016). These amphipods were measured from the anterior margin of the rostrum until the posterior margin of the cephalothorax (head), in lateral view (cephalothorax length, CL in mm) using a micrometer eyepiece in a stereoscopic microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet some environmental and biotic factors, could also have contributed for that, for example, a greater susceptibility of one of the genders to predation, which is directly related to the difference in sizes and behaviour. Although females of Crangonyx pseudogracilis are larger than males, males must find females to mate, thus being more exposed to predators (Jacobucci and Leite, 2006;Castiglioni et al, 2016). Additionally, a study by Watts et al (2002) revealed that the exposure of amphipods to certain chemicals present in the residual water, such as 17a À ethinylestradiol or also known as environmental estrogen (EE), can favour females more than males, resulting in a marked difference in proportions between the genders.…”
Section: Discussionmentioning
confidence: 99%